Development of a knowledge-based medical expert system to infer supportive treatment suggestions for pediatric patients - Ertugrul, Duygu Celik; Ulusoy, Ali Hakan (Wiley, 2019)
This paper discusses the design, implementation, and potential use of an ontology-based mobile pediatric consultation and monitoring system, which is a smart healthcare expert system for pediatric patients. The proposed system provides remote consultation and monitoring of pediatric patients during their illness at places distant from medical service areas. The system not only shares instant medical data with a pediatrician but also examines the data as a smart medical assistant to detect any emergency situation. In addition, it uses an inference engine to infer instant suggestions for performing certain initial medical treatment steps when necessary. The applied methodologies and main technical contributions have three aspects: (a) pediatric consultation and monitoring ontology, (b) semantic Web rule knowledge base, and (c) inference engine. Two case studies with real pediatric patients are provided and discussed. The reported results of the applied case studies are promising, and they demonstrate the applicability, effectiveness, and efficiency of the proposed approach.
Keywords: inferencing; mobile consultation and monitoring; ontology knowledge base; pediatric diseases; rule-based medical expert systems; smart healthcare systems